Heuristic Approach to Workforce Scheduling with Combined Safety and Productivity Objective - Nanthavanij, Suebsak; Yaoyuenyong, Sorawit; Jeenanunta, Chawalit (International Journal of Industrial Engineering: Theory, Applications and Practice, 2010)
<span style="font-family: ";Times New Roman";; font-size: 10pt; mso-fareast-font-family: 'MS Mincho'; mso-bidi-font-family: 'Angsana New'; mso-font-kerning: 1.0pt; mso-ansi-language: EN-US; mso-fareast-language: JA; mso-bidi-language: AR-SA;">The workforce scheduling with combined safety and productivity objective is introduced. Typically, industrial workers are assigned to perform a set of tasks with certain safety/ergonomics hazard. To reduce their hazard exposures, it is recommended that workers be rotated among the tasks periodically within each day so that the hazard exposures do not exceed a permissible limit. Since workers have unequal skill levels, this job rotation practice can affect total system productivity. Thus, assigning the right workers to the right tasks in each period can help to increase the productivity and, at the same time, achieve the safety objective. In this paper, we present a safety-productivity workforce scheduling model. From a given numerical example, we compare the optimal solutions obtained from the productivity-based, safety-based, and safety-productivity workforce scheduling models. A heuristic approach to the workforce scheduling with combined safety and productivity objective is also developed for solving large-sized problems.